PENGEMBANGAN LAGU BUDDHIS ANAK SEBAGAI MEDIA PEMBELAJARAN MATA PELAJARAN PENDIDIKAN AGAMA BUDDHA KELAS V - Putra, Yushua Adi; Ekowati, Wilis Rengganiasih Endah; Parsiyono, Parsiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This study aims to make songs and find out the process of making children's Buddhist songs as a medium of learning in the subject of Buddhist Education in the fifth grade. The research conducted is a research and development using the ADDIE with details of the process: 1) analysis includes: preliminary studies, needs analysis, material analysis; 2) design includes: making song lyrics and making an initial cover design of the album cover; 3) development including making music, making album cover designs and improving products based on advice from advisers and experts. The percentage of material experts is 89.05% which shows that the material contained in the product is very feasible to be applied to students. The percentage by music experts is 76.5% which means that the product developed is suitable to be a learning medium); 4) implementation includes limited product trials to teachers and students. The results of trials from teachers showed a percentage of 86.87% with very decent criteria and the results of trials from students showed a percentage of 90% with very decent criteria; and 5) evaluation includes evaluation of the product after the trial.